2017
DOI: 10.1183/13993003.02309-2016
|View full text |Cite
|
Sign up to set email alerts
|

Resistance profile of drugs composing the “shorter” regimen for multidrug-resistant tuberculosis in Brazil, 2000–2015

Abstract: The difficulties in managing multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant (XDR) TB are well known. The regimens are very expensive, often toxic, and require up to 24 months to achieve an acceptable probability of success [1-3]. Based on successful experiences in different settings, the World Health Organization (WHO) recently provided recommendations on the prescription of a new "shorter" regimen to treat MDR-TB, which is also known as the "Bangladesh regimen" [4-8]. The regimen is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…The WHO criteria preventing the use of the "shorter regimen" include [12,28,29,62,76,[83][84][85][86][87][88][89][90][91][92][93]: 1) confirmed resistance or presumed ineffectiveness to a medicine in the shorter MDR-TB regimen; 2) exposure to ⩾1 second-line medicines in the shorter MDR-TB regimen for >1 month; 3) intolerance to ⩾1 medicines in the shorter MDR-TB regimen or risk of toxicity (e.g. drug−drug interactions); 4) pregnancy; 5) extrapulmonary disease; and 6) at least one medicine in the shorter MDR-TB regimen not available.…”
Section: Notesmentioning
confidence: 99%
“…The WHO criteria preventing the use of the "shorter regimen" include [12,28,29,62,76,[83][84][85][86][87][88][89][90][91][92][93]: 1) confirmed resistance or presumed ineffectiveness to a medicine in the shorter MDR-TB regimen; 2) exposure to ⩾1 second-line medicines in the shorter MDR-TB regimen for >1 month; 3) intolerance to ⩾1 medicines in the shorter MDR-TB regimen or risk of toxicity (e.g. drug−drug interactions); 4) pregnancy; 5) extrapulmonary disease; and 6) at least one medicine in the shorter MDR-TB regimen not available.…”
Section: Notesmentioning
confidence: 99%
“…Publications from Europe have reported eligibility rates ranging from 6.2% to 14% [7][8][9][10]. Data from Pakistan and Brazil showed more optimistic eligibility rates of 50% or higher [11,12]. A multicountry population-based survey showed that, although pyrazinamide resistance was significantly associated with rifampicin resistance, this drug might still be effective in 19-63% of patients with rifampicin-resistant TB, and that the worrisome high level of ofloxacin resistance in Pakistan ( probably reflecting extensive, unregulated use of fluoroquinolones in some parts of Asia) was tempered by the negligible levels of resistance to fourth-generation fluoroquinolones documented in all survey sites [13].…”
mentioning
confidence: 99%
“…The scientific debate is presently focused on the proportion of suitable patients in some geographical settings and on the impact on the MDR-TB epidemic [27][28][29][30][31][32].…”
Section: The Updated Who Mdr-tb Guidelinesmentioning
confidence: 99%